THE IMPLEMENTATION OF PEER ASSESSMENT IN ONLINE WRITING CLASS AT SENIOR HIGH SCHOOL IN BAWEAN - Amalia, Nur Zikri (RETAIN, 2021)
Peer assessment is a kind of assessment process for the students who share the works and asks their peer to give feedback as their function as a group and use the feedback to revise and improve their work. Moreover, this study is aimed to explore how the teacher trains the students to do peer assessment in online writing class, how the teacher explains the rubric for peer assessment in online writing class, how the students implement peer assessment in online writing class, and how the teacher does the follow up task after the students implement peer assessment in online writing class. Qualitative-basic interpretive study was applied in this study to answer the research questions. Furthermore, field notes were used as the instrument of this study. Field note ware used to take note all information about how the implementation of peer assessment was running in the online writing class. The researcher observed the teacher’s and students’ verbal behavior and documents in order to discover the implementation of peer assessment in online writing class. This research was conducted in two meetings. The finding of this study showed that in the training stage, the teacher was still at the stage of explaining the definitions and benefits of peer assessment for students, not the stage of training students to conduct peer assessment. In explaining the rubric used, the teacher did not explain the criteria and description consisted in the rubric. The teacher only explained the benefits of the rubric for students in peer assessments process and the aspects that students should assess on the peer’s writing results. Students implemented peer assessment after the teacher sent the soft file of rubric to their group. In the peer assessment process, the students were also lack of discussion with the peers. Moreover, the teacher provided feedback as a form of teacher’s follow-up task on student writing results. In sum, the finding of this study showed that the implementation of peer assessment in online writing class was still ineffective. Keywords: peer assessment process, online writing class, training, rubric, follow-up task.